Factors Effecting Intimate Partner Violence among Pregnant Women at a Centre in Karnataka - Ramalingappa, Padmasri; Somya, KP; Akhila, MV (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the prevalence of intimate partner violence among pregnant women and to evaluate associated sociodemographic factors. Methods: This is a prospective cohort study which was carried out in the outpatient department, antenatal and labour wards among 635 antenatal women above 34 weeks of gestation. A pretested questionnaire was used and women were divided into two groups based on presence or absence of intimate partner violence. The sociodemographic details of the women were taken in both groups and data were analyzed for statistical significance using SPSS version 16. Results: The incidence of intimate partner violence was 52.8% out of which 30.7% were positive for physical violence, 23.4% for sexual violence and 46.3% for emotional violence. Sociodemographic factors like lower socioeconomic status, Hindu religion, economically not independent, unemployed husband, problems with in-laws, dowry at marriage, alcoholic and smoker spouse was associated with significantly more domestic violence (p<0.05). Conclusions: Iintimate partner violence is not uncommon and under reported.